PENGARUH KERJASAMA TIM, DISIPLIN KERJA, DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN YANG DIMEDIASI OLEH BUDAYA KERJA: (Studi Kasus Karyawan Koperasi PNM Tlogowungu Bagian Lapangan) - Imda Putri, Agna; Rauly Sijabat; Qristin Violinda (STIE-PMCI, 2023)
This study aimed to investigate the influence of teamwork, discipline, and job burden on employee performance at a cooperative in PNM Mekar, Kabupaten Pati. The quantitative research method was used, with a sample size of 288 respondents. The results showed that teamwork, discipline, and job burden significantly affected employee performance. Additionally, culture played a role in employee performance and helped mitigate the effects of teamwork, discipline, and job burden on performance. Hypotheses 1, 2, 3, and 4 were accepted, while hypothesis 5 was rejected. Hypotheses 6 and 8 were also accepted, but hypothesis 7 was rejected. In summary, the study found that these factors had a significant effect on employee performance, and there was evidence of the cultural effect on employee performance.